PELAKSANAAN KETERAMPILAN BERBICARA DI SENTRA BERMAIN PERAN DI TAMAN KANAK-KANAK ISLAM NIBRAS: THE IMPLEMENTATION OF SPEAKING SKILLS IN THE ROLE-PLAY CENTER AT NIBRAS ISLAMIC KINDERGARTEN - Diah Islamiarty; Yulsyofriend (Universitas Islam Malang, 2023)
The research background is that the language development of Islamic kindergarten children in Nibras develops well in speaking, it is proven that after the child it is evident that the child is able to speak well and clearly. The research purpose is to describe skills of speaking by children, describe the process of implementing role-playing center learning in developing children's speaking skills, describe the learning media in implementing the skills of speaking by children, describe the evaluation used by teachers in implementing the skills of speaking by children, and describe the methods used on children's speaking skills. talking child. The method used is a qualitative approach. In this research, the techniques for data collection used were: observation, interviews, and documentation. The techniques for data analysis used in research are reduction of data, display of data, and conclusion drawing (verification). The results shown that the planning for the implementation of children's speaking skills had been prepared referring to the independent curriculum and learning indicators, the implementation of well-stimulated children's speech skills supported by the methods and media teacher used, as well as the evaluation of the implementation skills of speaking by children seen from the child coming to school until the child went home school.